Safety aspects and side-effects of ExEm-gel and foam for uterine cavity distension and tubal patency testing - Exalto, Niek; Stassen, Mario; Emanuel, Mark Hans (Reproductive biomedicine online, 2014)
•Safety and side effects of ExEm®-gel and ExEm®-foam were reviewed.•Information on clinical use in the human and experiments in animal models was collected.•The influence of components on sperm cells, oocytes and blastocyst development was studied.•No serious side effects or concerns on safety of ExEm®-gel and foam were observed.•ExEm®-gel and foam are considered to be safe for intrauterine application and tubal patency testing. A state-of-the-art overview of the safety and side-effects of ExEm-gel for uterine cavity distension and ExEm-foam for tubal patency testing is presented. A literature search was carried out using PubMed, textbooks, pharmaceutical databases and reports of toxicity tests. Information on clinical use in humans and experiments in animal models was collected and grouped according to the following components: glycerol, hydroxyethyl cellulose and purified water; subjects included toxicity test, influence on sperm cells, oocytes, blastocyst development, uterine cavity distension, tubal patency testing, pain and obstetric applications. No unknown side-effects of gel or foam, or unexpected concerns about safety, were reported. More information than expected was available on the absence of effects of the components on various human tissues. Although it is difficult to prove that the search is complete, and it is possible that side-effects remain unreported, the combination of glycerol, hydroxyethyl cellulose and purified water is considered to be safe for intrauterine application and tubal patency testing, indicating an optimal risk–benefit ratio in clinical use. The safest strategy, however, is to restrict clinical examinations with gel and foam to the pre-ovulatory phase of the menstrual cycle.